Stability of yield and its components in garden pea (Pisum sativum) - PAN, R S; KRISHNA PRASAD, V S R; RAI, MATHURA (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the winter season of 1994, 1995 and 1996 to study the stability parameters, viz regression coefficient (bi) and mean square deviations (S2di) from linear regression, along with per-se performance of 9 varieties or lines of mid-season pea (Pisum sativum L., s.1.) for 7 yield-related characters. Linear and non-linear components of genotype x environment (G x E) interactions were high and low, respectively, for green pod yield. However, non-significant G x E (linear) interaction and significant pooled deviation for days to 50% flowering, pod length, pod breadth, seeds/pod, 100-green seed weight and shelling (%) indicated preponderance of non-linear component of G x E interaction. ’KS 226’ was better performing, stable and suitable for favourable environments for green pod yield (15.3 tonnes/ha), pod length (9.3 cm), seeds/pod (6.8) and 100-green seed weight (48.9 g) and suitable for unfavourable environment for pod breadth (1.5 cm). ’VL 6’ performed the best regarding green pod yield (17.8 tonnes/ha) and seeds/pod (6.9) and was stable and suitable [or favourable environments. ’Azad P 1’ was better performing. and stable for pod length (9.3 cm) and 100-green seedÂ weight (59 g) and was also stable for pod brelldth (1.5 cm) and responsive in unfavourable environments. ’Bonneville’ was better performing and stable for 100-green seed weight (51.4 g) and suitable for favourable environments, whereas ’RPM 34-2’ was better performing and stable for shelling (51.8%) and showed average response to change in envirorunental conditions.